Mass in Right Iliac Fossa- Clinicopathogical Evaluation - Tasleem Akhtar ,Atif Sharif ,Mumtaz Akhtar ,Naeem Zia ,Muhammad Hanif (Journal of Rawalpindi Medical College, 2017)
To identify clinico-pathological entities presenting as mass in right iliac fossa. Methods: In this observational study patients of mass in right iliac fossa were recruited. All patients who presented with sign and symptoms of mass in right iliac fossa were investigated and subjected to conservative or operative managements depending upon the cause and response to conservative management. Results: Appendicular mass (33.7%) was the commonest finding, followed by cecal carcinoma(9.8%), ileocecal tuberculosis(9.8%), psoas abcess (7.6%), retroperitoneal dermoid(3.3%), worm infestation (3.3%) and lymphoma (3.3%). Conclusion: Appendicular mass is the main cause of mass in right iliac fossa, with a wide range of other causes.